SAM II measurements of Antarctic PSC's and aerosols - Mccormick, M. P.; Trepte, C. R. (1986)
Measurements by the SAM II satellite instrument show that polar stratospheric clouds (PSC's) are a regular feature of the austral winter season in either nonvolcanically or volcanically disturbed periods. The tops of these clouds are observed above 20 km in early winter and descend in altitude over the course of the season to heights near 15 km in mid September. Typically, PSC's persist in the lowest stratospheric altitudes throughout September. Subsequently, October always represents a relative annual minimum in aerosol extinction above 15 km and in stratospheric column amount. In addition, volcanically produced aerosols in Antarctica peaked in early 1983 and, if linearly related to ozone losses, are probably not a contributing factor to the continued loss of total ozone in the Antarctic spring in 1984 and 1985.